Fundamental evaluation of Electrochemically Mediated Amine Regeneration: Application to Natural Gas Sweetening - Massen-Hane, Michael Edward Lev (Curtin University, 2020)
This thesis uses quantum chemical simulations and electrochemical methods to determine whether an electrochemically mediated amine regeneration (EMAR) cycle using ethylenediamine and copper is a viable alternative to the thermal amine systems used for acid gas removal from natural gas. This thesis then uses process models to compare the energy required by EMAR and thermal systems.